Analisis Sosiologi Sastra dalam Novel Hujan Bulan Juni Karya Sapardi Djoko Damono - Lelet, Angelina; Karouw, Stella M.; Imbang, Djeinnie (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTThis research is entitled "Sociological Analysis of Literature in the Novel Hujan Bulan Juni written by Sapardi Djoko Damono". This research discusses the sociological approach through intrinsic elements and social phenomena that occur in novels. The purpose of this study is to identify, classify and analyze the intrinsic elements used by the author in relation to social phenomena in Sapardi Djoko Damono's novel Hujan Bulan Juni. The research data was taken from a collection of words contained in the novel. The data is then analyzed using Semi theory. The method used in this research is qualitative method. The results of this study found intrinsic elements related to social phenomena in the novel Hujan Bulan Juni, where in this novel there are two main characters, namely Sarwono and Pingkan who experience differences in the background of education, social status, religion and culture in which the two figures always fighting together. But with the limitations they experience, they cannot deny it because this happens along the line of life. So that in the end they can only accept the fact that they cannot unite.Keywords: Intrinsic element, Social phenomenon, Novel â€œHujan Bulan Juniâ€.